2019
DOI: 10.1088/1402-4896/ab080e
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic AC magnetic susceptibility analysis of FeSe crystals with composite morphology

Abstract: The AC magnetic response of multi-domain FeSe crystals has been explored by means of fundamental and third harmonic AC magnetic susceptibility (ACMS) analysis. Our previous studies have revealed a complex morphology which especially modifies the mixed state properties. The effects were expressed by an additional 'pseudo' peak feature of the magnetic hysteresis and in the present study we analyze its vortex dynamics nature and irreversibility behavior in the context of ACMS. We find that the effect is detectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…This work deals with the AC magnetic response of an YBCO thin film by studying the imaginary component of the AC susceptibility. The choice to perform and measure the AC susceptibility derives from the fact that this technique is very sensitive to the presence of granularity in the superconductors because it can reveal the complex electromagnetic properties of the granular structure of materials [26][27][28][29][30][31][32][33][34][35]. In particular, the AC susceptibility has been studied as a function of the AC amplitude χ 1 ′′ (h AC ), the temperature χ 1 ′′ (T), and the DC magnetic field χ 1 ′′ (H DC ).…”
Section: Introductionmentioning
confidence: 99%
“…This work deals with the AC magnetic response of an YBCO thin film by studying the imaginary component of the AC susceptibility. The choice to perform and measure the AC susceptibility derives from the fact that this technique is very sensitive to the presence of granularity in the superconductors because it can reveal the complex electromagnetic properties of the granular structure of materials [26][27][28][29][30][31][32][33][34][35]. In particular, the AC susceptibility has been studied as a function of the AC amplitude χ 1 ′′ (h AC ), the temperature χ 1 ′′ (T), and the DC magnetic field χ 1 ′′ (H DC ).…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that a further analysis of the complex AC susceptibility data allows one to obtain the London penetration depth and therefore the superfluid density, thus enabling the validation of theories and models concerning the mechanisms of superconductivity in the IBS. For this goal, the high frequency of this technique offers an advantage with respect to conventional AC susceptometry, for which the determination of is challenging [ 16 ] because of the long wavelength and the geometry associated with those experiments [ 17 ], which is more suitable for the study of vortex physics and pinning [ 18 , 19 , 20 ] and of nonlinearity [ 21 , 22 ]. In Section 3 of this paper, we present and discuss the characterization of several IBS systems, belonging to different IBS families.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these different regimes causes an AC magnetic response generating fundamental and superior harmonic curves with complex shapes [21,23,24]. In particular, the third harmonic has the strongest signal (after the fundamental one) and for this reason it is the most analyzed also because it gives direct information on the vortex dynamics of the sample [25][26][27][28][29][30]. In the present study, we analyze the ACMS of a Fe(Se,Te) system belonging to the 11 family of the IBS, which is particularly interesting due to its very high value of the upper critical field and of the critical current density even at high magnetic fields [9,31,32].…”
Section: Introductionmentioning
confidence: 99%